Five-year results of a prospective, randomized, controlled study evaluating treatment of intra-bony defects with a natural bone mineral and GTR - Frank Schwarz, Anton Sculean
Background: Treatment with a natural bone mineral (NBM) and a guided tissue regeneration (GTR) has been shown to promote periodontal regeneration. However, until now there are only very limited data on the long-term clinical results following this regenerative technique. Aim: To present the 5-year results of a prospective, randomized, controlled clinical study evaluating the treatment of deep intra-bony defects either with open flap debridement (OFD) and a combination of an NBM and GTR (test) or OFD alone (control).